Lipidomic studies of membrane glycerolipids in plant leaves under heat stress. (July 2019) - Higashi, Yasuhiro; Saito, Kazuki
Abstract: Environmental stresses cause membrane damage in terrestrial plants. Studies on the lipids obtained from these plants are required to understand their adaptation to climate change. Recently, a number of plant leaf lipidomic studies converged on the topic of chloroplastic glycerolipid remodeling and triacylglycerol production. In this review, we show that among various abiotic stresses, plant leaves under heat stress specifically increase the levels of galactolipids containing linoleate (18:2) in chloroplasts; phospholipids containing palmitate (16:0), stearate (18:0), and oleate (18:1) in the endoplasmic reticulum and plasma membrane; and triacylglycerol containing α-linolenate (18:3) and hexadecatrienoic acid (16:3) as lipid droplets in the leaves of Arabidopsis thaliana . Recent studies have proposed responsible genes for the lipid remodeling under heat stress, highlighting the importance of the catabolic process of chloroplastic monogalactosyldiacylglycerol. This review comprehensively describes glycerolipid compositional changes in plant leaves under heat stress detected by lipidomic analyses and compares them with those under other abiotic stresses. We will discuss the physiological significance underlying the observed lipid metabolism under heat stress. Detailed knowledge about plant lipid remodeling can aid in the development of solutions to deal with the consequences of climate change, including global warming.